2019
DOI: 10.1039/c8ta08870e
|View full text |Cite
|
Sign up to set email alerts
|

Rational design and construction of nanoporous iron- and nitrogen-doped carbon electrocatalysts for oxygen reduction reaction

Abstract: This review pays specific attention to the design and synthetic strategies of Fe-N/C materials with porous structures and their merits towards ORR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(95 citation statements)
references
References 128 publications
0
95
0
Order By: Relevance
“…Heteroatom doping, which can induce partial charge change on the neighboring carbon, is regarded as a research frontier in boosting the ORR electrochemical efficiency of carbon materials [54,55]. Up to now, nitrogencontaining carbon-based nanostructures, such as N-doped graphene and N-containing carbon nanotube or nanofiber, have been widely demonstrated to display superb catalytic activity in fuel cells [56][57][58][59]. Additionally, in 2018, N-doped GDY was also reported to have outstanding ORR catalytic activity with rapid kinetics and remarkable half-wave potential of E 1/2 = 0.87 V under alkaline condition, which is comparable to that of commercial Pt/C catalysts (E 1/2 = 0.86 V) [60].…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatom doping, which can induce partial charge change on the neighboring carbon, is regarded as a research frontier in boosting the ORR electrochemical efficiency of carbon materials [54,55]. Up to now, nitrogencontaining carbon-based nanostructures, such as N-doped graphene and N-containing carbon nanotube or nanofiber, have been widely demonstrated to display superb catalytic activity in fuel cells [56][57][58][59]. Additionally, in 2018, N-doped GDY was also reported to have outstanding ORR catalytic activity with rapid kinetics and remarkable half-wave potential of E 1/2 = 0.87 V under alkaline condition, which is comparable to that of commercial Pt/C catalysts (E 1/2 = 0.86 V) [60].…”
Section: Introductionmentioning
confidence: 99%
“…Templated carbon materials have been prepared by various approaches, such as direct carbonization from carbon precursors and soft‐ and hard‐templating methods . To enhance the electrochemical performance of electrode materials, heteroatoms (e.g., nitrogen (N), sulfur (S), and boron (B)) have been doped into porous carbons …”
Section: Introductionmentioning
confidence: 99%
“…[8] To enhance the electrochemical performance of electrode materials, heteroatoms (e.g.,n itrogen (N), sulfur (S), and boron (B)) have been doped into porous carbons. [9] However,t he large-scale synthesis of NPC is difficulti nt erms of cost-effectiveness because these methods require numerous synthesis steps. To overcome these shortcomings, researchers have tried to solve the issues by using metal-organic frameworks (MOFs) as sacrificial templates or precursors.…”
Section: Introductionmentioning
confidence: 99%
“…For ORR electrocatalysts, some review articles have also been reported to discuss the influence of the morphologies of the related electrocatalysts . We limit our focus on the overview of the latest developments in M−N−C ORR electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[37,38] For ORR electrocatalysts, some review articles have also been reported to discuss the influence of the morphologies of the related electrocatalysts. [39][40][41][42][43] We limit our focus on the overview of the latest developments in MÀ NÀ C ORR electrocatalysts. Herein, the MÀ NÀ C electrocatalysts used for ORR were summarized from the point view of morphology.…”
Section: Introductionmentioning
confidence: 99%